Multi Level Marketing (MLM) dalam Pandangan Hukum Ekonomi Islam - Syaharuddin, Syaharuddin (Jurnal Iqtisaduna, 2023)
This research aims to look at the views of Islamic Economic Law regarding the implementation of Multi Level Marketing (MLM) in the business world. Apart from that, we will also look at the characteristics and characteristics of Multi Level Marketing (MLM) which are in accordance with the views of Islamic Economic Law. This research is a qualitative descriptive study, which attempts to provide an overview of the characteristics of Multi Level Marketing from the perspective of Islamic economic law which originates from the Koran and the Hadith of the Prophet. Data collection techniques by quoting directly and indirectly from references and related literature. The data processing and analysis techniques are qualitative descriptive in nature from existing data which is then interpreted to draw conclusions which give rise to implications and recommendations. The results of the research obtained show that Multi-level Marketing (MLM) is permissible as long as it does not conflict with the principles of muamalah.